NUB1 reduction promotes PCNA-mediated tumor growth by disturbing the PCNA polyubiquitination/NEDDylation in hepatocellular carcinoma cells - Dongnian Du; Wenming Zhang; Dandan Zhang; Lingpeng Liu; Jiajuan Li; Zehao Chen; Xuzhe Yu; Miao Ye; Wei Wang; Zijing Li; Jianghua Shao (Cell Death and Disease)
Abstract Negative regulator of ubiquitin-like protein 1 (NUB1), an inhibitor of neural precursor cells expressed developmentally downregulated 8 (NEDD8), is implicated in tumor growth. However, the expression of NUB1 in hepatocellular carcinoma (HCC) and its effects on HCC growth remain unclear. In this study, our findings revealed reduced NUB1 protein expression in HCC tissues and cells, leading to increased proliferating cell nuclear antigen (PCNA) protein stability through upregulating NEDD8 to promote HCC cell growth. Mechanistically, NUB1 reduction upregulated NEDD8 to promote PCNA NEDDylation at lysine 164 (Lys164), in turn, antagonized PCNA K48-linked polyubiquitination, thereby increasing the stability of PCNA in HCC cells. Finally, the results of the in vitro and in vivo experiments revealed that the NEDDylation inhibitor TAS4464 could inhibit PCNA NEDDylation to decrease PCNA protein expression, thereby suppressing HCC cell growth. Collectively, our results identified NUB1 as a negative regulator of HCC proliferation and confirmed that PCNA NEDDylation promotes PCNA protein stability by antagonizing PCNA polyubiquitination. This study provides a new perspective on the specific mechanism of HCC growth. It expands our understanding of the role of NEDDylation in the regulation of substrate proteins and their functions.